Faktor-Faktor yang Mempengaruhi Hubungan Kerja Sama Keamanan Militer Pakistan-Tiongkok: Implikasi terhadap Stabilitas Regional Kawasan Asia Selatan - Putri Dia Nina Sa’pang; Agussalim Burhanuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Pakistan and China have established cooperative relations in various fields for centuries. In the field of security, the two countries have formed military cooperation that has significantly impacted regional security stability and has been quite effective in addressing evolving security challenges and geopolitical tensions in South Asia. Using descriptive methods, researchers can describe the factors influencing military cooperation between Pakistan and China and examine its implications for regional stability in South Asia. The research findings indicate that Pakistan-China military cooperation is influenced by economic, political, and other military aspects, which subsequently provide a strong position for both countries to face various potential threats affecting the balance of power and stability in South Asia. This cooperation can create a balance of power that stabilizes the region and brings strategic benefits to both countries, though the risks of escalation and increased tensions are also consequences that must be managed carefully.